Modelling the process of sedimentation with the use of numerical methods - Kolodziejczyk, K. (Видавництво Національного університету “Львівська політехніка”, 2005)
The aim of works, which are contained in the article, is checking the correctness and the quality of simulation of sedimentation process reached results with the use of numerical methods. The author wanted to determine on the level of differences between calculation results with the use of CFD methods and results reached in the real system. These simulations were to give the answer if it is possible to apply the software FLUENT for simulation of the sedimentation process and how big error will appear.